Lex Orandi, Lex Credendi : a Church juridical inquiry in-to the sacramental liturgies of the Christian Reformed Church in North America - Faber, Ryan Lee (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.